2020
DOI: 10.1002/anie.202002452
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Research and Evaluation Models of Nanomotors for Cancer Combined Therapy

Abstract: Limited tumor permeability of therapeutic agents is a great challenge faced by current cancer therapy methods. Herein, a kind of near infrared light (NIR)‐driven nanomotor with autonomous movement, targeted ability, hierarchical porous structure, multi‐drugs for cancer chemo/photothermal therapy is designed, prepared and characterized. Further, we establish a method to study the interaction between nanomotors and cells, along with their tumor permeability mechanism, including 2D cellular models, 3D multicellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
87
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(88 citation statements)
references
References 54 publications
0
87
0
1
Order By: Relevance
“…Previous research has demonstrated that active delivery carriers with motile properties could significantly improve tissue penetration, enhance delivery efficiency, and enable effective therapy . A light‐responsive nanomotor prepared by mesoporous‐macroporous silica and Pt was demonstrated to be able to penetrate into three dimensional (3D) spheroids deeply for combined cancer therapy …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that active delivery carriers with motile properties could significantly improve tissue penetration, enhance delivery efficiency, and enable effective therapy . A light‐responsive nanomotor prepared by mesoporous‐macroporous silica and Pt was demonstrated to be able to penetrate into three dimensional (3D) spheroids deeply for combined cancer therapy …”
Section: Resultsmentioning
confidence: 99%
“…The efficacy of nanomotors for cancer combination therapy was evaluated in detail through two‐dimensional (2D) cellular models, three‐dimensionals (3D) multicellular tumor spheroids (MTSs) and in vivo models. This work initially proposed the possible penetration mechanism of physical nanomotors and further established the research model of the interaction between nanomotors and cells and the mechanism of tumor penetration, which provided a reliable and comprehensive paradigm for micro/nanomotors in cancer treatment [51] . Nevertheless, it must be mentioned that the thermal effect of NIR light brought the limitation of use time in a certain extent [47a,48,49] .…”
Section: Physical Micro/nanomotormentioning
confidence: 99%
“…[29,30] To solve these problems, Wan et al designed mesoporous-macroporous silica/platinum (Pt) nanomotor loaded with doxorubicin (DOX) for chemotherapy and Pt nanoparticles for photothermal propulsion and therapy. [31] This work established a systematic research model of nanomotors for synergistic therapy. However, the random loading of Pt nanoparticles leads to their weak asymmetric distribution, decreasing thermophoretic force.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric carbon core of mC@SiO 2 can form a thermal gradient under the NIR light irradiation, which propels nanomotors by self‐thermophoretic force. Notably, different from aforementioned NIR light‐driven nanomotors prepared by gold deposition and Pt nanoparticles loading, [ 27–31 ] the photothermal component of the nanomotor is carbon semi‐yolk inside the nanoparticle. Thus, the outer spiky shell can be totally used to load drug, resulting in a high loading capacity of DOX (596 µg mg −1 ).…”
Section: Introductionmentioning
confidence: 99%